A Comparison of Heritability Estimates by Classical Twin Modeling and Based on Genome-Wide Genetic Relatedness for Cardiac Conduction Traits. (17th October 2017) - Nolte, Ilja M.; Jansweijer, Joeri A.; Riese, Hariette; Asselbergs, Folkert W.; van der Harst, Pim; Spector, Timothy D.; Pinto, Yigal M.; Snieder, Harold; Jamshidi, Yalda
Abstract : Twin studies have found that ~50% of variance in electrocardiogram (ECG) traits can be explained by genetic factors. However, genetic variants identified through genome-wide association studies explain less than 10% of the total trait variability. Some have argued that the equal environment assumption for the classical twin model might be invalid, resulting in inflated narrow-sense heritability ( h 2 ) estimates, thus explaining part of the 'missing h 2 '. Genomic relatedness restricted maximum likelihood (GREML) estimation overcomes this issue. This method uses both family data and genome-wide coverage of common SNPs to determine the degree of relatedness between individuals to estimate both h 2 explained by common SNPs and total h 2 . The aim of the current study is to characterize more reliably than previously possible ECG trait h 2 using GREML estimation, and to compare these outcomes to those of the classical twin model. We analyzed ECG traits (heart rate, PR interval, QRS duration, RV5+SV1, QTc interval, Sokolow-Lyon product, and Cornell product) in up to 3, 133 twins from the TwinsUK cohort and derived h 2 estimates by both methods. GREML yielded h 2 estimates between 47% and 68%. Classical twin modeling provided similar h 2 estimates, except for the Cornell product, for which the best fit included no genetic factors. We found no evidence that the classical twin model leads to inflated h 2 estimates. Therefore, our study confirms the validity of the equal environment assumption for monozygotic and dizygotic twins and supports the robust basis for future studies exploring genetic variants responsible for the variance of ECG traits.